The potential of exopolysaccharide-producing bacteria from rhizosphere of rubber plants for improving soil aggregate - Nasrul Harahap; Dwi Andreas Santosa; Nuni Gofar (Brawijaya University, 2018)
This study aimed to examine the effect of bacteria found in the rhizosphere of rubber plants in producing exopolysaccharides to improve aggregate stability of sandy soils. Samples of soil have been taken in rhizosphere of rubber plants in West Kalimantan. Serial soil samples were diluted and cultured on ATCC no.14 medium to select potential bacteria to produce exopolysaccharides. Forty-five isolates of exopolysaccharide-producing bacteria isolated from the rhizosphere of rubber plants was inoculated on ATCC no.14 medium. Based on the observations of morphological colony of these isolates, most of them had similarities in colour and shape so that only ten different isolates were obtained based on the morphological colony. Ten isolates were re-grown on MacConcey medium. Three isolates formed thick or slimy mucus when cultured on MacConcey medium. Three isolates grown on the medium of ATCC 14 resulted in dry weight of exopolysaccharide (mg/mL) varying from 0.28 to 7.59 mg/mL with sucrose and glucose as carbon sources. The results of the molecular identification of the three isolates of Klebsiella sp. LW-13, Klebsiella pneumoniae strain DSM 30104 and Burkholderia anthina strain MYSP113 showed that Klebsiella sp. LW-13 and Burkholderia anthina strain MYSP113 with 2% organic matter increased soil aggregate stability from highly unstable (30.67%) to unstable (45.01-48.20%). This aligned with the results by scanning electron microscopy (SEM) on treated soil and without bacteria treatments.